Extreme Cyclones Entering the Arctic From the North Atlantic in Winter: Classification and Impacts - Junmei Lü; Zhirou Zhang; Minghu Ding; Junming Chen; Lan Xia; Wenqian Zhang (International Journal of Climatology, 2026)
The North Atlantic constitutes the primary pathway for winter cyclones intruding into the Arctic, and these cyclones are typically much more intense than those formed locally. When extreme cyclones penetrate the Arctic, they transport water vapour and heat to the north, inducing pronounced anomalies in weather and sea ice. Based on objective trajectory analysis, three distinct types of extreme cyclones were identified according to their tracks from the North Atlantic to the Arctic: Type 1 and Type 2 cyclones intrude into the seas west and east of Greenland and the Arctic Ocean, respectively, while Type 3 cyclones migrate along the European continent margin. This research investigates the associated anomalies in Arctic atmospheric circulation and sea ice in response to these trajectories. The results reveal that the three types of extreme cyclones are linked to distinct circulation anomalies, characterised by polar vortex splitting, Arctic Oscillation, and polar vortex displacement. Furthermore, Type 1 and Type 2 cyclones favour warming from troposphere to lower stratosphere, whereas Type 3 cyclones are conducive to cooling in both troposphere and stratosphere. Preliminary analysis suggests that prior to and during the early stages of cyclone development, dynamic wind effects in the lower troposphere drive sea ice southward, reducing sea ice in the polar regions while increasing it in lower latitudes. Moreover, warm air advected northward by the cyclone promotes sea ice loss, whereas the intrusion of cold air in the cyclone's rear sector enhances sea ice formation.